Carnosine Synthase (TsATPGD) Alleviates Lipid Peroxidation Under Transcriptional Control by an Nfe2-like Gene in Tridacna Squamosa - Zhuo Yang; Nai-Kei Wong; Fan Mao; Siwei Wu; Wenjie Yi; Ziniu Yu; Yang Zhang (Antioxidants)
As an important mollusk in reef ecosystems, Tridacna squamosa forms pro-survival symbiotic relationships that hinge on an exquisite redox equilibrium between the host and the photosynthetic symbiont, zooxanthellae. The exact regulatory mechanisms thereof remain poorly understood. In this study, a novel Nfe2-like transcription factor in T. squamosa was identified and characterized with respect to its antioxidant and cytoprotective roles. Gene structure and phylogenetic analysis reveal that T. squamosa possesses a single transcription factor TsNfe2l in contrast to mammalian Nfe2l1 (Nrf1) and Nfe2l2 (Nrf2), belonging to protein members of the bZIP-NFE2 subfamily and functionally resembling the mammalian Nfe2l1. A conserved bZIP domain permits its binding to the antioxidant response element (ARE) in vitro and in HEK293T cells. Further analyses such as promoter prediction suggest that TsNfe2l target genes engage mainly in the regulation of multiple enzymes involved in antioxidation and allied pathways. Notably, TsNfe2l transcriptionally upregulates carnosine synthase (TsATPGD), which subsequently produces L-carnosine abundantly to shield cells from oxidative damage. Moreover, the blockage of TsNfe2l nucleic acid binding reduced the expression of TsATPGD and L-carnosine content in the gill, resulting in elevated lipid peroxidation. Collectively, our findings establish novel molecular insight into TsNfe2l as a critical regulator of redox homeostasis in T. squamosa through carnosine synthesis.